My wilderness: the Pacific West. - Douglas, William O. (William Orville), 1898-1980 (Doubleday, 1960)
Justice Douglas writes of the Sierras, the Olympics, the Rain Forest of the Cascades, and other wild and beautiful western mountains and forests.